MUSIC AND SOCIETY: संगीत और समाज - Saxena, Seema (International Journal of Research -GRANTHAALAYAH, 2015)
The basic principle of nature is that Manushya determined the support of society for his natural needs, he had to create a society or go to the shelter of society to escape from his share of happiness and practical force and insecurity. In childhood, puberty, old age, or it should be said that at every stage of life, the need of society is natural to man. If the society is a mother, then the person is her child. Continuing on the path of progress from the initial stage of development, he started creating his own needs and this became the origin of the art of creation. प्रकृति का मूल सिद्वान्त है कि मनूष्य ने अपनी नैसेर्गिक आवष्यकताओं के लिये समाज के अवलम्ब को अवधारित किया उसे अपने सुखःदुख की हिस्सेदारी एवं व्यवहारिक बल व असुरक्षा से बचकर के लिये समाज की सृष्टि करनी पड़ी अथवा समाज की शरण में जाना पड़ा। बाल्यकाल, युवावस्था, वृद्वावस्था, अथवा यह कहा जाये कि जीवन के प्रत्येक चरण में मनुष्य को समाज की आवष्यकता नैसर्गिक होती है। समाज यदि जननी है तो व्यक्ति उसका बालक। विकास की प्रारंभिक अवस्था से निरन्तर प्रगति पथ पर बढ़ते हुऐ उसने अपनी आवष्यकताओं के रूप सृजन करना आरंभ किया और-यही सृजन कलाओं का उद्गम स्थल बना।